Network analyses of foreign travelers through Wallachia, Moldavia and Transylvania between 1831-1840 - PETRUȘ, Andrei (Studia Universitatis Babeș-Bolyai Digitalia, 2021)
Foreign travelers backgrounds alongside journey routes followed into Romanian Lands between 1831-1840 were placed into a database and mapped into different geographical, social or chronological visualizations in a unique approach for Romanian historiography. Making use of Nodegoat, a platform that allows researchers to compile large databases and to analyze these data, relying on network-type connections, I created various easy-readable and modellable graphs which shows differences and similarities between travelers. Less effort is now needed for complex analysis which could have taken weeks or months back then, because all of these were made by the platform within few clicks with the help of various filters. Building profiles and comparing them, analyses traveler’s studies according to professions and seeking for their motivation behind journey and travel path followed are just some of the analyses made by this project. Even though it comprehend only 46 travelers from a decade this project have a great potential in near future by integrating all of the volumes coordinated by Paul Cernovodeanu into a single database.